THE EFFECT OF THE MODELING METHOD ON THE 7TH GRADE STUDENTS’ LEARNING OUTCOMES IN DRAWING ANIMALS - Ferdiyana, I Gusti M.; Pakasi, Ruddy; Katoppo, Meki J. (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study aims to determine the effect of the application of the modeling method on the learning outcomes of drawing animals of seventh grade students at SMP Negeri 13 Dumoga. The pre-experimental design used is static group comparison design. In this study the treatment was given to the experimental class and the control class as a comparison. Data collection was carried out by giving a drawing test after treatment, the assessment was carried out twice by an assessor. Data analysis or statistical tests in this study were carried out using SPSS. The results of the statistical group showed the average experimental data of 15.9250 with a standard deviation of 1.16161, and the control class averaged 14.5250 with a standard deviation of 0.52503. The independent samle t test results show a t-value of 4.912 with a significance level of -0.000 smaller than 0.05. The statistical test results show that at p (α) 0.05 with df38, the t-count of 4.912 is greater than the t-table of 2.021 based on the results of the study there is a difference in the learning outcomes of drawing animals in using the modeling method and students who use conventional methods, it can be concluded that the use of the modeling method has a more significant impact on the results of drawing animals.